Use of Organic Acid, Herbs and Their Combination to Improve the Utilization of Commercial Low Protein Broiler Diets - El-Hakim, A.S. Abd; Cherian, G.; Ali, M.N. (International Journal of Poultry Science, 2008)
Two experiments were conducted to investigate the growth performance, carcass characteristics, organ weights, plasma proteins and fecal N excretion in broilers fed a 18% crude protein diet supplemented with Thymus vulgaris, Curcuma longa, citric acid, lactic acid or their combinations. In the first experiment, 98 broiler chicks were fed a control diet or a control diet with 0.2% Thyme (TH), 0.2% Curcuma longa (CL), 0.2% Citric acid (CIT), 0.2% TH + 0.2% CL, 0.2% TH + 0.2% CIT, 0.2% CL + 0.2% CIT. In the second experiment, 98 broiler chicks were fed a control diet with 0.2% TH, 0.2% lactic acid (LAC), 0.2% CIT, 0.2% TH + 0.2% LAC, 0.2% TH + 0.2% CIT, 0.1% LAC + 0.1% CIT. Addition of 0.2% TH, or TH + CIT increased weight gain in 21 day-old birds in experiment 1 (p<0.05). Addition of supplements did not produce any significant increase in day 42 body weight. No significant effect of supplements on carcass characteristics, feed conversion, plasma proteins or organ weights were observed except for liver which was higher in birds fed CIT (experiment 1) (p<0.05). No difference was observed in the total protein, albumen or globulin in the plasma. No difference was noticed between dietary treatments on the percentage of fecal Nitrogen (N), AME or Nitrogen retention (NR). Although not significant, the birds fed TH + CL excreted 12.9% less fecal N than Control birds. Similarly, the NR was 13.25% higher in TH + CL when compared with Control birds. Considering the role of low protein diets in reducing feed cost and fecal N excretion, further studies are needed to evaluate the role of plant extracts and organic acids and their optimal levels for broiler birds fed a low protein diet that are raised under suboptimal commercial conditions.